Normal Shoulder Ultrasound: Anatomy and Technique - Gupta, Harun; Robinson, Philip (Seminars in Musculoskeletal Radiology, 2015)
Shoulder ultrasound (US) is one of the most common applications of musculoskeletal US due to the high incidence of rotator cuff disorders. It can be used effectively for the diagnosis of rotator cuff diseases, and several studies have shown very high sensitivity and specificity for rotator cuff tears comparable with that of MRI. Shoulder US has several advantages over MRI such as lower cost, comparatively easier availability, short examination duration, dynamic capability, and ability to perform guided injection at the same appointment. However, it depends on the skill of the operator and therefore requires a standardized detailed protocol to avoid errors in diagnosis. A symptomatic area–only focused examination should not be performed because it is not uncommon to have symptoms away from the actual site of pathology. Detailed understanding of what anatomy can be evaluated is required, and this article discusses the relevant anatomy covering the rotator cuff, subacromial bursa, and acromioclavicular joint. The equipment requirements and technique of examination of different anatomical structures with transducer positions and normal sonographic appearances are described. Pitfalls and artifacts associated with shoulder US are covered; understanding them is crucial to avoid misinterpretation of findings.
Keywords: shoulder; ultrasound; anatomy